Communication apprehension and level of anxiety in the medical students of Rafsanjan University of Medical Sciences - Zahra Hashemi; Nasrin Shokrpour; Mina Valinejad; Maryam Hadavi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Communication apprehension (CA) is the fear or anxiety about communicating. This study was designed to investigate the CA and its related factors in the medical students at Rafsanjan University of Medical Sciences (RUMS). MATERIALS AND METHODS: In this cross-sectional study, personal report of CA (PRCA-24) was administered to 340 medical and paramedical students to measure anxiety in four domains of large groups, small groups, public speaking, and dyadic interaction. Pearson's correlation and linear regression analysis were used to investigate the relationship between CA and the variables of birth order, number of siblings, and university entrance score. Data were analyzed using descriptive and inferential statistics (Chi-square and Kruskal-Wallis Test). RESULTS: CA in the dimension of public speaking was higher than the other dimensions. Evaluation of the economic stability and its relationship to CA indicated a significant difference among all the domains of the PRCA-24. There was a significant relationship between the scores of CA and the number of siblings (P = 0.001). Linear regression and Pearson's correlation tests indicated a significant correlation between the variables of birth order, number of siblings, and university entrance score. The correlation between the CA with dimensions of group discussion, interpersonal, speaking, and meeting was weak but significant (P < 0.01). CONCLUSION: Without communication, the materialization and development of the human community are not possible. This aspect is more evident and crucial in the healthcare industry. Based on the results of this study, the medical and paramedical students at RUMS have a medium-to-high level of CA. Therefore, it is of utmost importance to detect students with high CA to prevent further communication problems after graduation.